1996
DOI: 10.1007/bf00023864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of natural and induced genetic variation in Alstroemeria using random amplified polymorphic DNA (RAPD) markers

Abstract: We have used random amplified polymorphic DNA (RAPD) markers to study genetic variation in Alstroemeria. The first objective was to examine the discriminatory power of RAPD markers in different genotypes of Alstroemeria obtained by traditional breeding. All genotypes examined, including commercial Alstroemeria varieties, could be distinguished on the basis of their RAPD profiles. Progeny plants could be distinguished from their parents. A second objective of this study was to investigate whether RAPD markers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Nevertheless, RAPD technique has been inconclusive or ineffective in some species. For example, RAPD markers did not detect somaclonal variation in begonia plants regenerated from leaf explants treated with increasing concentrations of nitrosomethylurea (Bouman and De Klerk 2001) as well as X-ray-induced garlic mutants (Anastassopoulos and Keil 1996). The technique also has a lower reproducibility and reliability (Jones et al 1997) as well as less informative compared to amplified fragment length polymorphism (AFLP) markers thereby limiting its application in some species (Mulcahy et al 1993;Vos et al 1995).…”
Section: Random Amplified Polymorphic Dnamentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, RAPD technique has been inconclusive or ineffective in some species. For example, RAPD markers did not detect somaclonal variation in begonia plants regenerated from leaf explants treated with increasing concentrations of nitrosomethylurea (Bouman and De Klerk 2001) as well as X-ray-induced garlic mutants (Anastassopoulos and Keil 1996). The technique also has a lower reproducibility and reliability (Jones et al 1997) as well as less informative compared to amplified fragment length polymorphism (AFLP) markers thereby limiting its application in some species (Mulcahy et al 1993;Vos et al 1995).…”
Section: Random Amplified Polymorphic Dnamentioning
confidence: 98%
“…Genetic variation in mutants can be induced either by specific treatments with physical and chemical mutagens or by tissue culture, see Predieri (2001) and Roux (2004) for detailed reviews. Anastassopoulos and Keil (1996) referred to somaclonal variation as mutations in plants regenerated from tissue culture. Remarkably, it has also been observed that the frequency of expression of dominance is higher in somaclonal variation than in other forms of mutation (Larkin 1998;Yang et al 2010).…”
Section: Relationship Between Mutation Induction and Somaclonal Variamentioning
confidence: 99%
“…Em plantas ornamentais, já foram utilizados marcadores RAPD para o estudo da variabilidade genética de diversas espécies, como, por exemplo: Alstroemeria (ANASTASSOPOULOS & KEIL, 1996), crisântemo (WOLFF & PETERS- VAN RIJN, 1993), rosa (TORRES et al, 1993), lírio (YAMAGISHI, 1995), gérbera (DA MATTA et al, 2009), entre outras.…”
Section: Introductionunclassified
“…Alstroemeria is a monocotyledonous plant and has its centres of origin in Chile and Brazil (Aker & Healy, 1990). Breeding activities have resulted in modern hybrids of Alstroemeria with large and beautiful flowers (Anastassopoulos & Keil, 1996). Biotechnological strategies such as recombinant DNA technologies and genetic transformation could provide efficient approaches in Alstroemeria breeding, but the lack of a reliable regeneration system to generate transgenic plants has hindered the use of genetic transformation in Alstroemeria .…”
Section: Introductionmentioning
confidence: 99%